Persatuan Ulama Seluruh Aceh (PUSA) dan Reformasi Pendidikan Islam di Aceh, 1939-1952 - Septian Fatianda; Badrun Badrun (Local History & Heritage, 2022)
Islamic education in Aceh in the early 20th century was in a phase of significant decline. This setback was caused by various factors such as the repressive attitude of the Dutch government which always monitored all forms of the learning process in the dayah because it was feared that through the dayah there would be more rebels. This has an impact on a rigid learning system and only studies religious issues, western science is considered something that is forbidden to learn. This increasingly complicated situation poses a challenge for reformist-minded ulama who want to reform the face of Islamic education in Aceh. The Organization of the Association of All Aceh Ulama (PUSA) was finally established as an answer to all the anxiety about the decline in education in Aceh. The reform effort carried out by PUSA is to integrate the general education curriculum with the religious education curriculum. The unification of the vision of every school in Aceh to establishing a university to produce modern teachers.